Klimathall i Norrbotten : En jämförande studie av platser i biltestregionen - Andersson, Magnus; Bohman, Thomas (2014)
For nearly 40 years, municipalities in the northern Norrland has played an important role in the automotive industry. Since the early 1970s the automotive industry has brought vehicles to be tested to its limit in winter climate. Winter Testing of vehicles is a very important part of vehicle development. Many of the tests performed in the car testing region are made on ice tracks on frozen lakes. The car testing region consists mainly of the municipalities of Arjeplog, Arvidsjaur and Älvsbyn. In these municipalities about 4,000 vehicles are tested during the winter season. The car testing region had a turnover of almost one billion SEK in 2013.Winter Testing has started to become a bottleneck for many automotive and component manufacturers. Development times have been shortened along with an increasingly unpredictable outdoor environment, these are contributing factors to the bottleneck. To eliminate this bottleneck ideas for building a winter testing facility with a controlled indoor environment emerged. This so-called climate arena's goal is to enable the winter test of vehicles indoors year round.The work was written in collaboration with the association of winter testing operations, SPGA (Swedish Provingground Association).The purpose of this study was to suggest various potential sites for placement of a climatic arena and investigate mainly the geotechnical conditions for the various locations. The aim of this study was to present the possible placement options for SPGA and provide the foundation proposals for the different areas.Placement suggestions were developed in cooperation with the municipalities in the car test region and SPGA. To investigate the feasibility of the sites geotechnical field and laboratory investigations was conducted. Data was collected from previous geotechnical investigations in close proximity to the suggested sites. Weight sounding and sieving of soil material was performed to obtain a picture of frost susceptibility and geotechnical properties in the areas.In the area in ...